The performance of artificial intelligence (AI) as the future of inbound marketing - Vásconez, Andrés (mktDESCUBRE; Vol 1 No 20 (2022): Twentieth Edition (July - December)DO - 10.36779/mktdescubre.v1i20.769, 2022)
In an era of constant innovation, companies are implementing cutting-edge marketing strategies, specifically Inbound Marketing, which is creating opportunities for organizations with a wide range of digital interactive media, the research problem lies in the abundance of information on the Internet, which makes customers feel harassed, persecuted and harassed by brands, so the objectives are framed in optimizing time and resources through new tools such as artificial intelligence that allow them to be a competitive advantage in companies, and thus create value in their content in a personalized way, anticipating the needs and emotions of consumers and the development during the customer’s life cycle.The present investigation uses a descriptive methodology with the use of books and scientific articles as a primary source, specifically the methods: theoretical, empirical and historical - logical, which are closely linked to the information collected and the discovery of the problem, additional applied strategies are established. in the customer life cycle that guarantees success in business relationships. The results show that millions of buyers no longer go shopping in physical stores, but are literally shopping, all the time and anywhere, which is why digital advertising platforms, social media, social listening, and -commerce, chatbots, email marketing, writing, CRM. As conclusions, it was based that through the analysis of the buying habit in Ecuador and the incidence of the technological environment in the purchasing process, a different type of marketing is needed: personalized, automated, of opportunities that allows a brand differentiation focused on people. and not in goods – services.